Reading interest, efficiency and emotional state as determinants of secondary school students’ achievement in reading comprehension in Oyo State (2020)
The participants of the study were 250 SS II students selected from five public secondary schools in Oyo West Local Government Area of Oyo State. Four instruments were used for data collection for the study; Students' Reading Comprehension Achievement Test (r=.79), Questionnaire on Students Reading Interest (r=.76), Questionnaire on Students Reading Efficiency (r=.81) and Questionnaire on Students Emotional State (r=.78). Data collected were analyzed using Multiple Regression Analysis at 0.5 level of significance. The results revealed that reading comprehension positively correlates with reading efficiency (r= .308, p< 0.05), students’ emotional state (r = .751, p<0.05) and Students reading interest (r=.611, p<0.05). The results showed a coefficient of multiple regressions R = 0.185 and R-square = 0.34. This suggests that the three factors combined accounted for 34% (Adj.R2= .012) variance in the prediction of reading comprehension. There was no significant effect of the independent variables on the students’ reading comprehension, F (i) = 0.561 P>0.05. The most potent factor was students’ reading interest (Beta = .263, t= 1.789, P<0.05), followed by students; reading efficiency (Beta = .139, t= 1.613, P<0.05), except for students’ emotional state. Based on the findings of this study, it was recommended that English language teachers should create a friendly and supportive environment that will enhance students’ reading interest, efficiency and positive emotional state so that, they can read and comprehend